1994
DOI: 10.1016/0014-5793(94)80524-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in chlorosomes from Chloroflexus aurantiacus grown under different conditions support the BChl c‐binding function of the 5.7 kDa polypeptide

Abstract: Structurally different chlorosomes were isolated from the green photosynthetic bacterium Chloroflexus aurantiacus grown under different conditions. They were analysed with respect to variable pigment-protein stoichiometries in view of the presumed BChl c-binding function of the 5.7 kDa chlorosome polypeptide. Under high-light conditions on substrate-limited growth medium the pigment-protein ratio of isolated chlorosomes was several times lower than under low-light conditions on complex medium. Proteolytic degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…It has long been known that the CD spectra of the chlorosomes were affected by changes in growth conditions (45,46), changes in pigment composition (47), and the addition and redilution of a saturated hexanol (48). These observations indicating the high sensitivity of the CD spectral patterns to various perturbations seem consistent with our simulation also showing the high sensitivity of the CD spectra to the slight changes in the structural parameters.…”
Section: Discussionsupporting
confidence: 91%
“…It has long been known that the CD spectra of the chlorosomes were affected by changes in growth conditions (45,46), changes in pigment composition (47), and the addition and redilution of a saturated hexanol (48). These observations indicating the high sensitivity of the CD spectral patterns to various perturbations seem consistent with our simulation also showing the high sensitivity of the CD spectra to the slight changes in the structural parameters.…”
Section: Discussionsupporting
confidence: 91%
“…These proteins, all of which appear to be associated with the chlorosome envelope, are designated CsmN, CsmM, and CsmA, respectively; the genes encoding these three proteins have been cloned and sequenced (Theroux et al 1990;Niedermeier et al 1992). Minor proteins with apparent masses of 5.8 and 8 kDa are often observed in C. aurantiacus chlorosomes as well (Feick and Fuller 1984;Lehmann et al 1994). Minor proteins with apparent masses of 5.8 and 8 kDa are often observed in C. aurantiacus chlorosomes as well (Feick and Fuller 1984;Lehmann et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Of these three major proteins, homologs of CsmM and CsmN have not yet been identified in the chlorosomes of Chlorobium sp., but proteins similar to CsmA (and the closely related CsmE) are found in the chlorosomes of both types of green bacteria. The former polypeptide was identified as the ~ subunit of the B806-866 complex (Lehmann et al (1994), whose two genes have been cloned and sequenced by Watanbe at al. The former polypeptide was identified as the ~ subunit of the B806-866 complex (Lehmann et al (1994), whose two genes have been cloned and sequenced by Watanbe at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsmM and CsmN, with apparent molecular masses of 11 kDa and 18 kDa, respectively, are related to one another and are possibly more distantly related in sequence to the CsmC and CsmD proteins of C. tepidum (32,48,50 At least three other proteins are likely to occur in chlorosomes of C. aurantiacus (19). CsmO (Caur_1311) is a member of the CsmB/CsmF protein family and occurs in three sequenced Chloroflexi strains, and the predicted sequence matches the N-terminal sequence of a protein in chlorosomes (19,26). Frigaard et al (19) additionally identified CsmP (Caur_0142; 17.2 kDa) and CsmY (Caur_0356; 22.0 kDa) in chlorosomes prepared from C. aurantiacus j-10-fl.…”
Section: Discussionmentioning
confidence: 98%